Initial time difference strict stability of fractional dynamic systems - Yakar, Coşkun; Gücen, Mustafa Bayram (Springer New York, 2012)
We have investigated that initial time difference fractional strict stability criteria for unperturbed fractional differential systems with Caputo’s Derivative. We establish comparison results for unperturbed fractional differential systems with respect to another unperturbed fractional differential systems which have different initial position and initial time. © 2017 Elsevier B.V., All rights reserved.
Keywords: Differential equations; System stability; Comparison result; Fractional differential; Fractional dynamic systems; Initial time; Strict stabilities; Stability criteria